Demand aggregation for photovoltaic self-consumption - Vera Reis; Rita H. Almeida; José A. Silva; Miguel C. Brito (Energy Reports, 2019)
The mismatch between photovoltaic generation and residential load leads to relative modest rates of self-consumption of solar electricity unless expensive storage solutions are locally available. One alternative to batteries is the aggregation of demand of different prosumers, as the collective load diagram might be better adapted to the solar resource. This hypothesis is tested for empirical data from 18 dwellings and 3 small businesses in the city of Lisbon, Portugal. Results show that a relatively low number of dwellings and a local small shop with a PV system without any storage will reach 90% self-consumption rates at a much lower cost than an individually owned PV system with 1 kWh/kWp storage system.
Keywords: 330; Demand aggregation; Photovoltaics; Self-consumption; Solar community